Assessment of Municipal Organic Solid Waste, as a Potential Feedstock for Briquette Production in Kampala, Uganda - Abondio, Richard B.; Komakech, Allan J.; Kambugu, Robert K.; Kiggundu, Nicholas; Wanyama, Joshua; Zziwa, Ahamada; Kyamanywa, Samuel (Uganda. Journal of Sustainable Bioenergy Systems, 2020)
The current shortage of energy resources coupled with environmental degradation problems resulting from deforestation in Uganda has contributed to increased demand for renewable energy resources including municipal organic solid waste and agricultural residues. However, organic waste from Municipal Solid Waste (MSW) may contain contaminants that are harmful to public health and the environment. This study determined the heavy metal concentration in MSW in Kampala City, Uganda. Also, the physicochemical properties of briquettes produced from the MSW were compared with charcoal. The waste samples were collected from residential, institutional and market areas over a period of two weeks. They were then analyzed for the presence of heavy metals. Briquettes were made from the bio-waste and were subjected to calorific and proximate analysis. Results indicated that the mean concentrations of Cd, Cr, Cu, Fe, and Pb were 1.25 mg/kg, 2.04 mg/kg, 38.2 mg/kg, 3.97 mg/kg and 1.99 mg/kg respectively while Hg was not detected. The calorific values of briquettes ranged from 8.9 to 15.3 MJ/kg and were lower than those of charcoal. Heavy metal concentrations in bio-waste collected were below the permissible acceptable limits. These findings indicate that the sampled MSW does not pose a health hazard arising from the presence of such heavy metals and therefore could be a safe source of renewable energy
Keywords: Organic Waste; Heavy Metal Concentration; Briquettes